Integration policy in the agri-food chains: theory and empirical evidences - Gaetano MARTINO; Rossella PAMPANINI; Francesca MORBIDELLI (Agricultural Economics (AGRICECON), 2012)
The paper considers the problem of the organizational adaptation of the supply chain in the face of the emerging inducement to integration. We focus on the policy intervention aimed at achieving a closer coordination among the chain agents and consider the relation between the policy and the spontaneous processes undertaken by the agents. A framework based on four dimensions (state of alignment, enforcement procedures, responsibility and stability) is proposed. This framework supports the hypothesis that the effectiveness of the policy intervention depends on the possibilities of the existence of hybrid governance structures. We analyze the agents' attitudes toward integration and propose two case studies on two integration projects carried out in Central Italy. The results of our study corroborate the hypothesis and suggest that integration entails many supply chain management components. However, our findings suggest that the policy intervention may face limits due to the processes undertaken by the agents.